Detailed Fetal Anatomic Ultrasound Examination: Effect of the 2014 Consensus Report on a Tertiary Referral Center. Issue 1 (March 2019) - Fratto, Victoria M.; Chang, Aileen; Anton, Tracy; Sun, Heather Y.; Lamale-Smith, Leah M.; Pretorius, Dolores H.
Abstract : Abstract: This study evaluates the impact of extended cardiac views on examination time, repeat imaging, and anomaly detection before and after implementation of 76811 guidelines (American Institute of Ultrasound in Medicine Consensus 2014). It is a retrospective study of singleton pregnancies undergoing detailed ultrasound imaging at 18 weeks' gestation or greater before and after the protocol change in an academic, tertiary care fetal center. Views required prior to 2014: 4-chamber, left outflow tract, right outflow tract. Additional views required after 2014: bicaval, aortic arch, 3-vessel, and 3-vessel trachea. Fetuses with known anomalies were excluded. Rates of detection of congenital heart disease (CHD), examination completion, repeat examination recommendation, fetal echocardiogram recommendation, completion by body mass index, and cardiac examination time were determined. Six hundred twenty-four subjects were included, 217 before and 407 after protocol change. Views obtained were as stated in the American Institute of Ultrasound in Medicine/Society for Maternal-Fetal Medicine consensus. Detection of CHD was not improved. Examination times increased by 20% (6.4 vs 7.7 minutes, P < 0.05). Number of incomplete studies increased by 130% (11% to 26%, P < 0.05). Twice as many patients were referred for repeat examination (6% vs 13%, P < 0.05). Completion rates were negatively correlated with body mass index. Recommendations for fetal echocardiogram were unchanged (5% vs 6%, P = 0.6). Additional imaging did not increase detection rate of CHD (3% vs 2%, P = 0.3). Extended cardiac views resulted in increased examination time, more incomplete examinations, and more repeat examinations without changing detection rates of CHD.